Idiopathic intradural dorsal thoracic arachnoid cysts: A case series and review of the literature. (June 2017) - French, Heath; Somasundaram, Arjuna; Biggs, Michael; Parkinson, Jonathon; Allan, Rodney; Ball, Jonathon; Little, Nicholas
Highlights: Spinal intradural arachnoid cysts may be either idiopathic or acquired. Idiopathic cysts are a separate entity and their aetiology remains uncertain. IASCH and TIAC may have a similar radiological appearance. Dorsal TIACs commonly present as thoracic myelopathy. Cine-mode SSFP can help differentiate between dorsal TIAC and IASCH. Primary management for symptomatic TIACs is laminectomy and excision/fenestration. Surgery aims to further deterioration in patients with progressive gait ataxia. Patients with predominantly gait symptoms may show no improvement post treatment. Abstract: Background: Spinal intradural arachnoid cysts (SIAC) are cerebrospinal fluid (CSF) filled sacs formed by arachnoid membranes and may be either idiopathic or acquired. Idiopathic cysts represent a separate entity and their aetiology remains uncertain. By far the most difficult differential diagnosis is distinguishing between idiopathic anterior spinal cord herniation (IASCH) and dorsal thoracic intradural arachnoid cysts (TIAC), due to their similarity in radiological appearance. Cine-mode (SSFP) is emerging as a novel technique in the diagnosis and operative planning of SIAC. Method: Retrospective analysis of patients with idiopathic TIACs that were surgically managed at Royal North Shore Hospital and North Shore Private Hospital between November 2000 and November 2015. Results: Ten patients were included in this study. Age ranged from 20 to 77 years with a mean age of 60 years and a female preponderance. The most common clinical features were progressive gait ataxia and lower limb myelopathy. Radicular pain tends to improve following surgery, however gait ataxia may not. Discussion: While there are circumstances in which the distinction between dorsal thoracic intradural arachnoid cysts and idiopathic anterior spinal cord herniation are radiologically obvious, in cases where the appearances are less clear, cine-mode SSFP MRI imaging can provide an invaluable tool to differentiate these pathologies and lead the clinician towards the correct diagnosis and management. The mainstay of surgical management for dorsal TIACs is laminectomy and cyst excision or fenestration. Surgery for gait ataxia should be aimed towards preventing deterioration, while maintaining the potential for symptomatic improvement, whereas surgery for radicular pain should be curative.